Market chain analysis of candeia timber (Eremanthus erythropappus) - Oliveira, Antonio Donizette de (2009)
This study characterized and analysed the market chain of candeia timber intended for oil production, and estimated the marketing margin retained by each chain participant. The study site encompassed two regions of Minas Gerais state whose distinctive mark is great abundance of native candeia forest (Eremanthus erythropappus). Data were collected through interviews with rural workers, candeia woodland owners and manufacturers of candeia oil and alpha-bisabolol. The marketing margin was computed as the percentage retained by each chain participant on each kilo of alpha-bisabolol sold. It was concluded that alpha- bisabolol distributors are the participants reaping the greatest marketing margin, and also that rural producers should sell candeia timber directly to oil manufacturers, with no middlemen wholesalers, in order to boost their marketing margin.